Volume of red blood cell transfusion is a risk factor for acute ischemic stroke after non-variceal upper gastrointestinal bleeding - Zhou, Fan; Huang, Jiaming; Huang, Donghua (Frontiers in Neurology, 2025)
ObjectiveTo determine if the volume of red blood cell (RBC) transfusion is a risk factor for acute ischemic stroke (AIS) in patients with non-variceal upper gastrointestinal bleeding (NVUGIB).MethodsNVUGIB patients who received RBC transfusion between January 2019 and December 2021 were included. Patients were divided into two groups, AIS group and non-AIS group. Propensity score matching was used to match the confounding factors between the two groups. Multivariate logistic regression was used to analyze independent risk factor for AIS in NVUGIB patients. The ROC curve was used to assess the sensitivity and specificity of the factors.ResultsThe study included 272 NVUGIB patients who received RBC transfusions, with 44 patients in the AIS group and 228 patients in the non-AIS group. After propensity score matching, 38 pairs of patients were successfully matched. Multivariate logistic regression showed that the volume of RBC transfusion was an independent risk factor for AIS in NVUGIB patients. The area under the curve for RBC transfusion volume was 0.811, the sensitivity and specificity were 0.553 and 0.921, respectively.ConclusionThe volume of RBC transfusion is a risk factor for AIS in NVUGIB patients. However, these results need to be validated by multicenter, prospective studies with larger sample sizes.